Interaction and Transformation on Social Media: The Case of Twitter Campaigns. (January 2018) - Housley, William; Webb, Helena; Williams, Meredydd; Procter, Rob; Edwards, Adam; Jirotka, Marina; Burnap, Pete; Stahl, Bernd Carsten; Rana, Omer; Williams, Matthew
The increasing popularity of social media platforms creates new digital social networks in which individuals can interact and share information, news, and opinion. The use of these technologies appears to have the capacity to transform current social configurations and relations, not least within the public and civic spheres. Within the social sciences, much emphasis has been placed on conceptualizing social media's role in modern society and the interrelationships between online and offline actors and events. In contrast, little attention has been paid to exploring user practices on social media and how individual posts respond to each other. To demonstrate the value of an interactional approach toward social media analysis, we performed a detailed analysis of Twitter-based online campaigns. After categorizing social media posts based on action(s), we developed a typology of user exchanges. We found these social media campaigns to be highly heterogeneous in content, with a wide range of actions performed and substantial numbers of tweets not engaged with the substance of the campaign. We argue that this interactional approach can form the basis for further work conceptualizing the broader impact of activist campaigns and the treatment of social media as "data" more generally. In this way, analytic focus on interactional practices on social media can provide empirical insight into the micro-transformational characteristics within "campaign communication."